Efektivitas Vaksin Influenza terhadap Risiko Komplikasi Pneumonia pada Anak: Analisis - Subagio, Devina; Subagio, Devani (PT Kalbe Farma Tbk., 2025)
Influenza is an acute respiratory infection (ARI) caused by the influenza virus. World Health Organization (WHO) states that influenza virus infection causes 99% deaths in children under 5 years of age in developing countries. Transmission between individuals is fast because the influenza virus is transmitted through droplets. Symptoms of influenza disease vary; most are mild and self-limiting, but in some cases, it can cause severe complications and have an impact on mortality. Pneumonia is one of the most common complications of influenza, especially in the pediatric population. Influenza vaccination is an effective option for preventing infection and its complications. Several studies have shown that influenza vaccination can reduce influenza cases and the incidence of influenza-related pneumonia hospitalizations.